ASSESSMENT OF THE COMPETITIVENESS OF UKRAINE AND THE QUALITY OF LIFE OF THE POPULATION - CHEREP, OLEKSANDR; KURDUPA, VALERIYA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
International competition is a multifaceted market economic category that reflects the struggle of civilizations, regions, countries, global complexes and specialized industries, global and multinational companies, financial institutions and other actors in the global space for competitive advantage.The concept of international competitiveness is often used in the analysis of macroeconomic indicators of countries. It allows you to compare for the country and its trading partners, a number of significant economic characteristics that can help explain international trends in international trade. This concept includes, first of all, qualitative factors or factors that cannot be quantified.The high level of national competition determines the growing opportunities to attract investment to the country, technology transfer, expand market presence and sign new trade contracts for any country. Conversely, low ratings and feedback are indicators of underestimation by governments and the need to stimulate the improvement of the national environment. This can push companies to fight for markets.It is impossible to overcome the coverage of the problem without a detailed study of the concept of competitiveness and assessment of the main factors of the indicator.Competitiveness is one of the main indicators of state development. The problem of Ukraine's low level of competitiveness is quite relevant. It is characterized by low living standards, socio-political atmosphere in the country, the state and level of development of the financial system and production efficiency. The article examines the current level of competitiveness of the country and the quality of life of the population, formed the essence of this concept and identified its main quantitative characteristics, analyzed the potential of Ukraine for the future. This study analyzes the main features of the Ukrainian economy and its place against the background of the international economy on the basis of the world competitiveness rating. The main indices are considered, namely: the Ease of doing business index, the index of economic freedom in the country (Index of Economic Freedom) and The Human Development Index and the Investment Privatization. However, ways to increase Ukraine's competitive position in the international arena are proposed.
Keywords: competitiveness; standard of living; index of economic freedom; index of ease of doing business; index of global competitiveness; potential